Molecular design, synthesis and biological evaluation of novel 1,2,5-trisubstituted benzimidazole derivatives as cytotoxic agents endowed with ABCB1 inhibitory action to overcome multidrug resistance in cancer cells - Abeer H. A. Abdelhafiz; Rabah A. T. Serya; Deena S. Lasheen; Nessa Wang; Mansour Sobeh; Michael Wink; Khaled A. M. Abouzid (Journal of Enzyme Inhibition and Medicinal Chemistry)
Multidrug resistance (MDR) is a leading cause for treatment failure in cancer patients. One of the reasons of MDR is drug efflux by ATP-binding cassette (ABC) transporters in eukaryotic cells especially ABCB1 (P-glycoprotein). In this study, certain novel 1,2,5-trisubstituted benzimidazole derivatives were designed utilising ligand based pharmacophore approach. The designed benzimidazoles were synthesised and evaluated for their cytotoxic activity towards doxorubicin-sensitive cell lines (CCRF/CEM and MCF7), as well as against doxorubicin-resistant cancer cells (CEM/ADR 5000 and Caco-2). In particular, compound VIII showed a substantial cytotoxic effect in all previously mentioned cell lines especially in doxorubicin-resistant CEM/ADR5000 cells (IC50 = 8.13 µM). Furthermore, the most promising derivatives VII, VIII and XI were tested for their ABCB1 inhibitory action in the doxorubicin-resistant CEM/ADR 5000 subline which is known for overexpression of ABCB1 transporters. The results showed that compound VII exhibited the best ABCB1 inhibitory activity at three tested concentrations (22.02 µM (IC50), 50 µM and 100 µM) in comparison to verapamil as a reference ABCB1 inhibitor. Such inhibition resulted in a synergistic effect and a massive decrease in the IC50 of doxorubicin (34.5 µM) when compound VII was used in a non-toxic dose in combination with doxorubicin in doxorubicin-resistant cells CEM/ADR 5000 (IC50(Dox+VII) = 3.81 µM). Molecular modelling studies were also carried out to explain the key interactions of the target benzimidazoles at the ABCB1 binding site. Overall the obtained results from this study suggest that 1,2,5-trisubstituted benzimidazoles possibly are promising candidates for further optimisation and development of potential anticancer agents with ABCB1 inhibitory activity and therefore overcome MDR in cancer cells.